2014
DOI: 10.1111/pops.12175
|View full text |Cite
|
Sign up to set email alerts
|

Precision Weapons, Civilian Casualties, and Support for the Use of Force

Abstract: Precision weapons such as drones have become important elements of the military strategies of the United States and other countries. How does the use of precision weapons influence public support for the use of force?The public is averse to casualties, mission failure, and collateral damage. I argue that precision weapons increase the salience and importance of avoiding civilian harm. Individuals adopt their expectations about the outcomes of using these weapons and have lower tolerance for attacks that result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…While our results are not based on a representative sample, they still suggest that Turkish participants would appear to be critical of the U.S. drone program, but they are more supportive of the use of armed drones in general. This is in line with previous research which has emphasized the importance of features of the operational context for attitudes towards drone strikes (e.g., Faulkner Rogers, ; Walsh, ). As the previous survey of Turkish opinion referred to the U.S. drone program in nondesignated conflict areas, it seems plausible that the perceived international legitimacy of drone strikes is another such feature (Kreps, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While our results are not based on a representative sample, they still suggest that Turkish participants would appear to be critical of the U.S. drone program, but they are more supportive of the use of armed drones in general. This is in line with previous research which has emphasized the importance of features of the operational context for attitudes towards drone strikes (e.g., Faulkner Rogers, ; Walsh, ). As the previous survey of Turkish opinion referred to the U.S. drone program in nondesignated conflict areas, it seems plausible that the perceived international legitimacy of drone strikes is another such feature (Kreps, ).…”
Section: Discussionsupporting
confidence: 91%
“…In an experimental study, when the compatibility of drone strikes with international humanitarian law was problematized, U.S. participants were less supportive of drone strikes (Kreps, ). Research has also indicated that support for drone strikes may be affected by features of the operational context, such as the probability of civilian casualties and the characteristics of the target of the proposed drone strike (Beier, ; Faulkner Rogers, ; Walsh, ). Outside of the United States, little research has explored attitudes towards armed drones (see Fair, Kaltenthaler, & Miller, ; Faulkner Rogers, ), and most research has focused on support for U.S. drone strikes.…”
Section: The Social Representations Approachmentioning
confidence: 99%
“…Prior work tells us that pecuniary costs affect support for presidential belligerence (Flores-Macías and Kreps 2015; Geys 2010; Kriner et al 2015). Moreover, casualty levels-"the most salient cost of war" (Gartner 2008, 105)-have repeatedly been found to influence popular support for foreign intervention (Boettcher and Cobb 2006;Eichenberg 2005;Gelpi et al 2009;Karol and Miguel 2007;Kriner 2006;Walsh 2015). With this in mind, the vacation example's parallel in foreign policy opinion research is the possibility that the hypothetical scenario an experimental respondent reads might induce high-level, desirability concerns-like national reputation or leadership competence and consistency-while failing to account for low-level, feasibility concerns-higher taxes, American casualties, and other wartime stressors.…”
Section: Audience Cost Theory Meets Construal Level Theorymentioning
confidence: 99%
“…Governments are also constrained in their military actions by the need to gain support from their citizens and supporters. People are less willing to support military interventions when they think civilian casualties will be higher (e.g., Eichenberg, ; Kreps, ; Walsh, ), although this effect has been found to be modest and sensitive to context (Gelpi, Feaver, & Reifler, ). Larson and Savych () found that while people in the United States reported that the level of civilian casualties would affect their prior support for war, support during war was more affected by whether they thought the military was doing enough to avoid casualties.…”
Section: Civilian Casualties and Political Discoursementioning
confidence: 99%